2011
DOI: 10.1021/ar2000716
|View full text |Cite
|
Sign up to set email alerts
|

Extending NHC-Catalysis: Coupling Aldehydes with Unconventional Reaction Partners

Abstract: Transition metal catalysis is a powerful means of effecting organic reactions, but it has some inherent drawbacks, such as the cost of the catalyst and the toxicity of the metals. Organocatalysis represents an attractive alternative and, in some cases, offers transformations unparalleled in metal catalysis. Unique transformations are a particular hallmark of N-heterocyclic carbene (NHC) organocatalysis, a versatile method for which a number of modes of action are known. The NHC-catalyzed umpolung (that is, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
155
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 719 publications
(160 citation statements)
references
References 85 publications
3
155
0
2
Order By: Relevance
“…In addition, NHCs are often utilized as green and cheap organocatalysts in many C-C bond-forming reactions (benzoin condensation, Stetter reaction, etc.) [5][6][7][8][9][10][11].…”
Section: N-heterocyclic Carbenes (Nhcs)mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, NHCs are often utilized as green and cheap organocatalysts in many C-C bond-forming reactions (benzoin condensation, Stetter reaction, etc.) [5][6][7][8][9][10][11].…”
Section: N-heterocyclic Carbenes (Nhcs)mentioning
confidence: 99%
“…The possible utilizations of NHCs (generated from azolium salts and bases) as organocatalysts in organic synthesis is reported in a plethora of papers, summarized in classical and more recent significant reviews [5][6][7][8][9][10][11]. On the other hand, some authors suggested the electrochemical generation of NHCs by cathodic reduction of azolium cations.…”
Section: Umpolung and The Peculiar Chemistry Of Nhcsmentioning
confidence: 99%
“…Other activation strategies can be invoked by deprotonation of dialkyl imidazolium-based ILs with a base, thus generating an N-heterocyclic carbene (NHC) (Figure 1a). In synthesis, NHCs derived from solid thiazolium, imidazolium and triazolium salts (Figure 1b) have proven to be efficient metal-free catalysts for a vast number of chemical transformations [14][15][16][17][18][19][20][21]. Although dialkyl imidazolium salts constitute the basis for a large number of commercial ILs, the use of such as NHC precatalysts in synthesis is underutilized compared to their solid counterpart [22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, NHCs have drawn a lot of attention due to their unique reactivity and high selectivity in many different types of organocatalytic reactions [2][3][4][5][6]. Because NHCs exhibit a polarity reversal property also named umpolung reactivity [7,8], they have opened new avenues for the development of novel transformations. They are nowadays accepted as efficient tools in the field of organocatalysis [9][10][11] and have been thoroughly studied especially in the reactions of NHCs with activated olefins [12].…”
Section: Introductionmentioning
confidence: 99%